Pendampingan Masyarakat Peternak Ayam Broiler dalam Pemanfaatan Teknologi PLTS-PLN Hybrid pada Sistem Close House - Irvawansyah, Irvawansyah; Muhammad, Umar; Z, Sultan Mubarak (Forum Kerjasama Pendidikan Tinggi, 2026)
This Community Service (PkM) activity aims to improve the efficiency of PLN electricity usage in managing closed poultry houses (close house) through the application of Hybrid PLTS-PLN technology, IoT systems, and water filtration systems. The main problems addressed in this activity include the high electricity consumption of partner farmers in managing close house poultry facilities, poor water quality, and limited monitoring of the poultry houses, which previously relied only on blurred plastic sheets attached to the walls.The methods used in this activity consist of several stages, including problem identification, literature study, system design, fabrication, testing, installation, and dissemination of system usage to partners.The results of this activity show an efficiency improvement in electricity usage of 165,888 kWh per production cycle and 995.328 kWh annually, resulting in savings of Rp. 174,801.85 per cycle and Rp. 1,048,801.85 annually. In addition, the developed system successfully reduced mortality rates from 220 birds (5.5%) to 133 birds (3%), while also facilitating partner farmers in monitoring poultry house conditions through IoT-based CCTV and controlling lighting systems via smartphones.Challenges encountered during implementation included limited working time and long procurement durations for components, which were constrained by the availability of offline supplies.This activity provides both short-term and long-term impacts, as well as opportunities for further development of livestock technology implementation on a more complex scale using renewable energy in rural areas.